Carrot root size distribution in response to biostimulant application. (19th May 2017) - Szczepanek, Małgorzata; Wilczewski, Edward; Pobereżny, Jarosław; Wszelaczyńska, Elżbieta; Ochmian, Ireneusz
ABSTRACT: In 2009–2011, in Poland (53°13′N, 17°51′E), field experiments were conducted concerning the influence of biostimulants Kelpak SL and Asahi SL on the size grades of yield of carrot cv. 'Karotan'. Kelpak SL is produced from seaweed Ecklonia maxima ; Asahi SL is composed of nitrophenols. Biostimulants were sprayed from fourth-leaf stage of carrot, once, twice or three times in growing period. Seaweed extract was used at total doses of: 0, 2, 3, 4, 5, 6 and 7 l ha −1, while Asahi SL at 1 l ha −1 . It was found that biostimulants had a favourable effect on total and commercial root yield, but this effect was dependent on the type of preparation, the dose, the time and the number of treatments. The best results in increasing the commercial yield were achieved after a single application of Kelpak SL at doses 2 or 3 l ha −1 at the fourth-leaf stage (13.1% and 12.4% respectively, compared to the control). Both biostimulants Kelpak SL and Asahi SL positively affected the root size distribution by increasing the yield of medium roots (1.9–3.8 cm in diameter) as well as large roots (3.8–5.0 cm), by 30.5% and 15.8%, respectively.